Unraveling the atypical co-crystal transformation process and mechanism of CL-20 and HMX in solid propellant formulations - Pangangjing Zou; Shiliang Huang; Haobin Zhang; Shichun Li; Jie Li; Yu Liu; Liangbin Li; Jinjiang Xu (Journal of Materials Research and Technology)
The integration of CL-20 into solid propellants offers substantial potential for enhancing energy output, yet introduces critical challenges related to structural instability during multi-component blending, aging, and long-term storage. This work employs in-situ and off-line XRD, OM, and complementary analytical techniques to probe the atypical co-crystallization pathways governing the interaction between CL-20 and HMX in propellant formulations. Key findings demonstrate that CL-20 and HMX spontaneously form a thermodynamically stable 2:1 co-crystal (2CL-20/HMX) not only in nitrate ester plasticizers (e.g., DOS) but also within polymeric binders such as GAP and HTPE, contrary to the inert behavior observed in HTPB, AP, or Al-containing systems. Kinetic analysis further established that the co-crystal structure transformation process is rate-limited by nucleation barriers, consistent with a kinetically controlled transformation mechanism. Moreover, the interaction between CL-20 and HMX proceeds through a solvent-mediated interface dissolution-reorganization pathway, thermodynamically favored by energy minimization. These results provide a fundamental understanding of co-crystal structure transformation in composite solid propellants containing HMX and CL-20. The resolution of co-crystallization mechanisms advances the practical implementation of CL-20-based propellants by reconciling energy enhancement with structural reliability.